YOGA IS A SOLUTION FOR WEIGHT LOSS AND STRESS IN INSULIN RESISTANCE POLYCYSTIC OVARY SYNDROME (PCOS) - Zakkiyatus Zainiyah; Eny Susanti; M Suhron (STIKES NGUDIA HUSADA MADURA, 2022)
Polycystic Ovary Syndrome (PCOS) is an endocrine disorder that often occurs in women of reproductive age, which is characterized by menstrual disorders (amenorrhea/oligomenorrhea), hirsutism, acne, alopecia and increased androgen hormones (testosterone). Based on the 1990 National Institutes of Health diagnostic criteria, the prevalence of PCOS is 6 to 10% and the Rotterdam 2003 criteria for PCOS prevalence is around 4–6% of women of reproductive age. Based on research by Santoso and Irawan, 2007 the prevalence of PCOS in Surabaya in women of reproductive age is 4.5%. The method of community service is by collecting data on PCOS patients who have been examined by dr. obgyn with a diagnosis of PCOS at the local midwife at PMB Sri Andini, SST, Bd in Sepulu, Bangkalan, after that collecting all PCOS patients on a predetermined day and explaining the purpose from community service and counseling on simple ways to lose weight in PCOS patients, followed by weighing, measuring height and abdominal circumference or Waist Circumference and Waist to Hip Ratio (w/h), and conducting interviews by giving questionnaires, giving an explanation of the importance of weight loss for health with Yoga exercise which aims to improve blood circulation and improve health. Based on the results of Yoga management given 4 times a month, it was obtained from 10 patients 2 people who experienced weight loss and 8 people with fixed weight, and from stress, patients from moderate and severe stress experienced a decrease in mild or normal stress. Yoga is still given or practiced at home. Every 2 times a week.